Mapping research trends of insulin resistance in polycystic ovary syndrome from 2017 to 2021: A bibliometric analysis - Chen, Yong; Zhang, Qian; Ma, Jinhui; Yu, Yuexin (Frontiers in Endocrinology, 2022)
To explore the research progress and trend of insulin resistance (IR) in polycystic ovary syndrome (PCOS). With the theme of “Polycystic ovary syndrome” AND “Insulin Resistance”, the key data set of web of science core collection database from 2017 to 2021 was extracted and bibliometric analysis was performed. Through VOSviewer v1.6.10 software, the research trend in this field is analyzed visually. The analysis contents include annual published literature quantity, published countries, journals, authors, institutions, references and keywords. 1898 literatures about IR in PCOS from 2017 to 2021 were downloaded from the core data set of web of science. Among them, China is the country with the highest number of published articles. Shang Hai Jiao Tong University is the most prolific organization. Asemi Z is the most prolific author. The Journal of gynecological endocrinology has the highest number of published articles. The most cited reference is the revised Rotterdam standard (2004) for PCOS diagnosis. The key words are divided into six categories: (1) The interaction between insulin resistance and chronic inflammation and dyslipidemia; (2) The relationship between insulin resistance and metabolic syndrome and NAFLD; (3) The interaction between insulin resistance and hyperandrogenemia; (4) The relationship between insulin resistance and dyslipidemia; (5) Metformin may regulate insulin resistance in the treatment of PCOS; (6) The study of serum biomarkers in PCOS patients with insulin resistance. The six key words extracted can provide an in-depth perspective for the study of IR in PCOS, and provide valuable information to help researchers identify potential research directions, collaborators and cooperative institutions.